A CLINICAL AND RADIOLOGICAL STUDY OF THE ALVEOLAR PROCESS OF THE MANDIBLE IN DIFFERENT TYPES OF OCCLUSION IN PATIENTS AGED 7 TO 18 YEARS - Gusenov Серажудин; Budaychiev Марат; Abdumukhtarova Мадина; Abdufarukov Абдулрахим (International Journal of Scientific Pediatrics, 2025)
Relevance. Malocclusions, accompanied by overload or underload of individual teeth in a specific region of the jaw, can cause pathological changes in the alveolar process, similar to those observed in periodontal disease. In this regard, clinical and radiological examination of the alveolar process at different age periods and with different types of bite is of great importance. The purpose of the study was to investigate the clinical and radiological age-related features of the normal structure of the alveolar process of the mandible in children and adolescents aged 7 to 18 years. Materials and methods of the study. In the present study, we selected for clinical and radiographic examination of the alveolar process a total of 600 individuals aged 7 to 18 years with orthognathic occlusion; 50 individuals with excessive maxillary development complicated by deep incisal overlap (prognathism combined with deep bite); 42 individuals with excessive maxillary development without contact between the anterior teeth (prognathism combined with open bite); 50 individuals with deep incisal overlap (deep bite); and 22 individuals with open bite. Of the 600 individuals with orthognathic occlusion, 160 were examined twice, and 29 were examined three times at intervals of 1–2–3–4 years after the initial assessment. Results. In the four types of malocclusion examined in our study, the radiographic structure of the alveolar process was generally similar to that observed in individuals with orthognathic occlusion. Only in subjects with excessive maxillary development and absence of contact between the anterior teeth (prognathism combined with open bite) was an increased radiolucency of the trabecular structure of the interdental septa observed more frequently (in 25 out of 42 individuals). These features were found only in subjects aged 12 years and older, and only in cases where no occlusal contact between the anterior teeth was present even upon mandibular protrusion. Conclusion. The structure of the alveolar process during tooth eruption differs from its structure after eruption is complete. Following the completion of tooth eruption, individual variations in the morphology of the interdental septal crests and the trabecular bone pattern become evident. With the completion of root formation, the development of the cortical plate and the periodontal space is finalized.